Tobin’s Separation Theorem: Information from the Colombian Stock Market for the First Half of 2008 (2019)
This paper shows a special situation where a portfolio created based on Tobin’s separation theorem does not match the Markowitz efficient set. Next a review of Markowitz´s portfolio selection theory is offered, followed by a review of Tobin’s separation theorem. Next, these models are used as tools for the individual investor with data on the Colombian stock market of the first half of 2008. Finally, the conclusions are shown. It is important to emphasize that the objective of this paper is not to make predictions upon expected returns, variances and covariances of these returns, nor to suggest an optimal portfolio for an investor with a particular utility function, but to expose a concrete scenario in which Tobin´s theorem leads to a portfolio located outside Markowitz´s efficient set.